Efisiensi Garis Litigasi dan Garis Non Litigasi pada Penyelesaian Sengketa Batas Laut Indonesia Menurut Unclos 1982 - Albertus Agung Yonathan; Felix Thekno; Rasji Rasji (Publikasi Indonesia, 2022)
The purpose of this study is to investigate and analyze the causes of maritime boundary disputes in Indonesia as well as the efficiency of ITLOS in resolving such disputes. Using a statutory approach and a case approach, the author conducted normative legal research. Boundary disputes or disputes involving countries, islands or the sea can be resolved by international courts acting in accordance with international law. There are still many maritime boundary disputes, such as those concerning the Malacca Strait between Malaysia and Indonesia, the Natuna Sea area between Indonesia and Vietnam, the Exclusive Economic Zone (EEZ), the South China Sea, and other maritime boundaries. It is these unilateral claims that cause conflict in interstate relations. This can occur due to unresolved international negotiations, violations by one of the parties (countries), unclear sea boundaries, etc. UNCLOS 1982 is a United Nations Convention with a global reach that applies and only applies to countries that have ratified it. Maritime boundary disputes can be resolved in one of two ways: through litigation or through non-litigation. The last resort for resolving maritime boundary disputes is ITLOS. In Indonesia, resolving maritime boundary disputes through litigation has been more successful than resolving disputes through non-litigation.